Effects of feeding double strain spores as a probiotics with or without antibiotic growth promoter on broiler performance - Roy, Bibek Chandra; Khatun, Anguara (Asian Journal of Medical and Biological Research, 2020)
The objectives of the study were to investigate the effects of feeding probiotics supplemented diets with or without antibiotic growth promoter on growth performance, carcass characteristics and cost-effectiveness of commercial broilers. A gable type open sided house was used for experimental purpose. Three hundred twenty Cobb-500 one- day-old straight run chicks were randomly distributed into four dietary groups having five replications. The number of birds in each replication was 16. Four diets were considered: diet 1: control; diet 2: antibiotic growth promoter (AGP) at a dose of 15g/100kg; diet 3: probiotics (PB) at a dose of 250g/100kg and diet 4: AGP plus PB (15g/100kg+250g/100kg). Birds were vaccinated against common viral diseases as a part of disease prevention program. The records were kept of body weight, feed intake and mortality while weight gain, feed conversion ratio (FCR) and survivability were calculated. Both performance and carcass yield were statistically analyzed for interpretation. Broiler chicks that received PB showed significant improvement in performance (P<0.01) over control with respect to body weight gain, FCR, carcass yield and cost-effectiveness. Feeding AGP alone had comparatively less weight gain, net profit and almost similar feed efficiency compared with PB and AGP+PB groups but its performance was much better than that of control group. The PB fed group showed better meat yield traits. The PB alone group was also more cost effective over control. Feeding PB may be practiced in broiler diet as an alternative to AGP. Asian J. Med. Biol. Res. September 2020, 6(3): 400-407